Electrochemical Sensors Using Two‐Dimensional Layered Nanomaterials. Issue 5 (25th March 2015) - Su, Shao; Chao, Jie; Pan, Dun; Wang, Lianhui; Fan, Chunhai
Abstract Two‐dimensional (2D) layered nanomaterials, e.g. graphene and molybdenum disulfide (MoS2), have rapidly emerged in material sciences due to their unique physical, chemical and mechanical properties. In the meanwhile, there is a growing interest in constructing electrochemical sensors for a wide range of chemical and biological molecules by using these 2D nanomaterials. In this review, we summarize recent advances on using graphene and MoS2 for the development of electrochemical sensors for small molecules, proteins, nucleic acids and cells detection. We also provide our perspectives in this rapidly developing field.